DENSITY AND DISTRIBUTION PATTERN OF BIVALVES IN WATERS OF MALANG RAPAT VILLAGE, GUNUNG KIJANG DISTRICT, BINTAN REGENCY - Soehendrawan, Sherry Febrarismono; Lestari, Febrianti; Kurniawan, Dedy (AQUASAINS, 2022)
The purpose of this study was to determine the density, diversity, uniformity, dominance and distribution pattern of bivalves in the waters of Malang Rapat Village. This research uses purposive sampling method. Determination of the sampling point based on the consideration of activities in the waters of Malang Rapat Village. Sampling using a quadrant transect method measuring 1x1 meter. Â The results showed that the highest species density was Gafrarium pectinatum with a value of 63,333 ind/ha, and the lowest species was Pinctada radiata with a value of 1,111 ind/ha. The species diversity index obtained values in the range of 0.54-0.76 and the category of each station is low. The uniformity index is obtained with a value in the range of 0.56-0.76 and categories at stations I and III are medium, stations II and IV are high. The dominance index obtained values in the range of 0.22-0.42 and the category at each station are low, the dominant species was G. pectinatum with a value of 0.38. The distribution pattern of bivalves in the sea of Malang Rapat Village at stations I and 3 obtained values of 2.43 and 3.05 with clustered categories, while at stations II and IV obtained values of 0.07 and 0.48 with the same or uniform categories.